Collaborative metacognition effects on student problem-solving performance and learning attitude in chemistry - Salise, Joan G.
The study examined the effects of collaborative metacognition on students' problem-solving performance and learning attitude towards chemistry. It also investigated the relationship between problem-solving performance and learning attitude. Moreover, the study explored the perceived effects of collaborative metacognition on the problem solving experience of students. The study used the quasi-experimental two-group design that involves both quantitative and qualitative approaches. It was conducted in two intact, heterogeneous third year sections of a public national high school in Quezon City during the fourth quarter of the school year 2013-2014. Collaborative metacognition (CM) is a combination of three strategies: (1) grouping with three members of varied ability, (2) use of problem-solving prompts, and (3) writing a learning journal. The Problem-Solving Performance Test (PSPT), Learning Attitude Scale towards Chemistry (LASC), journal entries of students, and classroom observations of the teacher-observer were the sources of data in this study. The data were analysed and interpreted using t-tests in the PSPT and LASC scores, and Pearson product-moment of correlation for the relationship between the two independent variables. Moreover, qualitative analysis was done to explore the perceived effects of collaborative metacognition on the students' problem solving experience. The results of the study revealed that the students exposed to collaborative metacognition achieved significantly higher problem-solving performance considering that all the components of CM are new to them compared to students exposed to conventional teaching. However, the five weeks of intervention is too short for the student of CM group to develop scientific attitude in chemistry. Longer time of research implementation is recommended. It is important to note that whether an intervention is implemented or not, there is a positive correlation between problem-solving performance and lea